Taking care of the newborn dying and their families: Nurses' experiences of neonatal intensive care - Fabiane de Amorim Almeida; Mariana Salim de Moraes; Mariana Lucas da Rocha Cunha (SciELO, 2016)
Objective To understand the experiences of nurses when caring for dying newborns and their families in the NICU; and redeem their perceptions about acting before the death and grieving process. Method A descriptive exploratory study with a qualitative approach, developed with nine nurses at the ICU of a hospital in São Paulo (SP), Brazil. Data was collected through semi-structured interviews and analyzed using the Collective Subject Discourse (CSD). Results Caring for newborns who are dying and their families is very difficult for nurses, due to the intense involvement. They seek strategies to deal with the situation and, before the newborn's death, despite the suffering, express the feeling of accomplishment. Conclusions Facing death and grief triggers mechanisms that emerge life references, coming across painful issues. Learning to deal with these questions is a daily challenge for nurses of the NICU.